A coumarin‐based fluorescent probe for Hg2+ and its application in living cells and zebrafish. (23rd April 2020) - Li, Xiwei; Duan, Qingxia; Yu, Yamin; Wang, Kun; Zhu, Hanchuang; Zhang, Xue; Liu, Caiyun; Jia, Pan; Li, Zilu; Sheng, Wenlong; Zhu, Baocun
Abstract: Mercury (Hg) is a heavy metal with high toxicity and easy migration; it can be enriched through the food chain, and cause serious threats to the natural environment and human health. So, the development of a method that can be used to detect mercury ions (Hg 2+ ) in the environment, in cells, and in organisms is very important. Here, a new 7‐hydroxycoumarin‐derived carbonothioate‐based probe (CC‐Hg ) was designed and synthesized for detection of Hg 2+ . After addition of Hg 2+, a large fluorescence enhancement was observed due to the formation of 7‐hydroxyl, which reinforced the intramolecular charge transfer process. The CC‐Hg probe had good water solubility and selectivity. Moreover, the probe was able to detect Hg 2+ quantitatively over the concentration range 0–2 μM and with a detection limit of 7.9 nM. Importantly, we successfully applied the probe to detect Hg 2+ in water samples, in living cells, and in zebrafish. The experimental results demonstrated its potential value in practical applications.